Flexible reproductive seasonality in Africa-dwelling papionins is associated with low environmental productivity and high climatic unpredictability - Dezeure, Jules; Dagorrette, Julie; Burtschell, Lugdiwine; Chowdhury, Shahrina; Lukas, Dieter; Swedell, Larissa; Huchard, Elise (Peer Community Journal)

(untitled)
At a time when seasonal cycles are increasingly disrupted, the ecology and evolution of reproductive seasonality in tropical vertebrates remains poorly understood. In order to predict how changes in seasonality might affect these animals, it is important to understand which aspects of their diverse patterns of reproductive phenology are linked to either the equally diverse patterns of rainfall seasonality (within-year variations) or instead the marked climatic unpredictability (year-to-year variations) occurring across the intertropical belt. Here, we gather birth and climatic seasonality data from 21 populations of 11 Africa-dwelling primate species from the papionin tribe, occupying a wide range of environments, including equatorial, tropical, temperate and arid climates. We investigate (1) the environmental variations that influence the intensity of reproductive seasonality, and (2) the reproductive stage that is synchronized with increased resource availability. Our results demonstrate wide variation in the intensity of birth seasonality between and within species. Across multiple measures of climatic variation, we found rainfall unpredictability to be the only clear predictor of the intensity of reproductive seasonality across populations, i.e., greater year-to-year variation in the amount of rainfall was associated with lower to no reproductive seasonality. Finally, we identified diverse patterns of reproductive phenology, with the most seasonal breeders generally aligning lactation with the peak in resource availability while other populations show more diverse patterns, where conception, lactation or weaning can all be synchronized with maximal food availability. This study sheds new light on the extent and ecological drivers of flexible reproductive phenology in long-lived tropical mammals, and may even contribute to our understanding of why humans give birth year-round.